Improvement in nutrition quality of greengram (Phaseolus radiatus) as influenced by fertilization and inoculation - DHARI, D K; SHARMA, A; SINGH, LAL (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was carried out during the rainy (kharif) seasons of 1994 and 1995 at Allahabad, to assess the effect of graded levels of phosphorus, sulphur and Rhizobium inoculation on protein content and S-containing amino acid of green gram (Phaseolus radiatus L.). Application of graded doses of phosphorus, sulphur and inoculation enhanced the protein content in seed (21.59%). Significant increase in protein content (21.31 and 21.26 %) was observed up to 26 kg P and 20 kg S/ha. A significant positive infuence of Rhizobium was also noticed on protein content (21.22 %). The sulphur containing amino acids was highest (0.60, 0.70 and 0.51g /16 g N) at 30 kg S/ha and lowest under its absence (0.46, 0.57 and 0.]6 g/16 g N). For methionine, cystine and cysteine, an ap’plication of 20 kg S/ha was adequate to bring their concentration statistically on par with 30 kg S/ha. Rhizobium inoculation significantly increased (0.53g/16 g N) methionine content over its uninoculated treatment, while the cystine and cysteine contents remaincd unaffected due to inoculation.